A dated volcano‐tectonic deformation event in Jan Mayen causing landlocking of Arctic charr. (11th February 2021) - Larsen, Eiliv; Lyså, Astrid; Höskuldsson, Ármann; Davidsen, Jan G.; Nadeau, Marie J.; Power, Michael; Tassis, Georgios; Wastegård, Stefan
ABSTRACT: We provide the first documentation of tectonic deformation resulting from a volcanic eruption on the island of Jan Mayen. Vertical displacement of about 14 m southwest of the stratovolcano Beerenberg is associated with an eruption in ad 1732 on its southeastern flank. The age of the uplift event is bracketed by radiocarbon‐dated driftwood buried by material deposited due to uplift, and by tephra from this eruption. Constraints, inferred from radiocarbon ages alone, allow for the possibility that uplift was completed prior to the ad 1732 eruption. However, the occurrence of tephra in the sediment column indicates that some displacement was ongoing during the eruption but ceased before the eruption terminated. We attribute the tectonic deformation to intrusion of shallow magma associated with the volcanic eruption. Our results complement previous studies of volcanic activity on Jan Mayan by providing precise age constraints for past volcanic activity. Also, it raises new hypotheses regarding the nature, timing and prevalence of precursor tectonic events to Jan Mayan eruptions. The uplift caused the complete isolation of a coastal lake by closing its outlet to the sea, thus landlocking the facultative migratory fish species Arctic charr (Salvelinus alpinus).